Oral exposure to Staphylococcus aureus enterotoxin B could promote the Ovalbumin-induced food allergy by enhancing the activation of DCs and T cells - Yuan, Jin; Tong, Ping; Meng, Xuanyi; Wu, Yong; Li, Xin; Gao, Jinyan; Chen, Hongbing (Frontiers in Immunology, 2023)
Recent work highlighted the importance of environmental contaminants in the development of allergic diseases. The intestinal mucosal barrier, Th (helper T) cells, DCs (dendritic cells), and intestinal flora were analyzed in the present study to demonstrate whether the exposure of enterotoxins like Staphylococcus aureus enterotoxin B (SEB) in allergens could promote the development of food allergy. We found that co-exposure to SEB and Ovalbumin (OVA) could impair the intestinal barrier, imbalance the intestinal Th immune, and cause the decline of intestinal flora diversity in OVA-sensitized mice. Moreover, with the co-stimulation of SEB, the transport of OVA was enhanced in the Caco-2 cell monolayer, the uptake and presentation of OVA were promoted in the bone marrow dendritic cells (BMDCs), and Th cell differentiation was also enhanced. In summary, co-exposure to SEB in allergens should be considered a food allergy risk factor.